Penggunaan Sekresi Kutu Lak pada Pembuatan Biokomposit dari Sabut Kelapa - Hermawan, Axel Adam; Ariesta, Axl; Ilcham, Adi; Murni, Sri Wahyu (Eksergi, 2021)
Nowadays, biocomposite materials are required for particular needs. Coconut husk has a potential to be biocomposite using a resin produced by the laccifer lacca kerr (kerria lacca), an insect. This work was aimed to study the use of the lacca kerr resin to produce a biocomposite of coconut coir based. In the experimental, firstly, the cleaned coconut husks were chopped then mixed with lacca kerr resin and alcohol to make a composite dough. Then the dough were pressed with 130 psig at a 100oC within15 minutes. After that, the biocomposite was allowed to ambient temperature, then it properties were observed. To find the best product properties, the ratio of basic materials were varied. The ratio of coconut husk: lacca kerr resin was used ranged from 0.6 g/mL to 1.4 g/mL. The characterization of product properties were carried out based on ASTM D-638 and under guidance of the Indonesian National Standard (SNI) 03-2105-2006. Based on results, it was found that the best biocomposite observed had properties such as density of 0.45 g/cm3 , water content of 8.8% (maximum SNI requirement of 14%), degree of swelling of 67.6%, tensile strength of 43.4 kgf / cm2 (minimum SNI requirement of 3, 1 kgf / cm2 ), Young's modulus of 1219.2 kgf/cm2 , elongation of 67.7%, conductivity of 1.8 10-8 /.m. Some of these characteristics have met the Indonesian national standard (SNI).